Point discharge current and its dependence on potential gradient and wind speed - GUPTA, J. P. (MAUSAM, 1975)
The study of point discharge current has been made using an isolated metallic sharp point raised above the earth's surface, A theoretical relation between the point discharge current, wind speed and the potential gradient has been derived and the results have been compared with experimental observations.